Possibility of Preparing Thematic Maps Through Developing of the Geographic Information System (GIS) - Stjepan Husnjak; Matko Bogunović (Kartografija i Geoinformacije, 2013)
It is a well known fact that nowadays planning of sustainable development and land use requires a lot of reliable and good quality information, which serves as the basis for timely and adequate decision-making. One of the most important forms of information is presented in various maps. Until recently, preparing of such data was, no doubt, a rather complex and time-consuming task. However, at present, thanks to, first of all, the GIS technology it is possible to develop corresponding geographic information systems with databases which then allow comparatively simple and quick preparing of necessary thematic maps. The paper first presents the method of developing the Geographic and Land Information System (GLIS) of the Karlovac County which, although developed for the purpose of agricultural development, may also be used in the development of forestry, environment protection, physical planning, water management and for soil conservation and regulation. Several examples illustrate the possibilities of preparing of specialised maps based on this GLIS. The basic data for developing of the geographic and land information system were the data of the Basic Soil Maps and topographic maps of the Republic of Croatia at the scale of 1:50 000 or 1:25 000, and the data from other studies made for the purpose of agricultural development in the area. These data, together with the results of processing and analysing of this data, by digitalisation, generalisation and interpolation, were incorporated into an integrated database of the geographic and land information system by using Microstation, AutoCad, ArcInfo, ArcWiew and Access software and the corresponding hardware. GLIS database consists of two parts. The first part includes the data referring to polygons - pedological contours, and the other part the data on pedological profiles. The base is organised in a way that enable the preparation of different thematic maps, but it can be also used in digital form allowing simple and easy access by the ArcWiew program package to all information, either by the base search or by putting questions. The data included in the database are the basis for preparation of numerous specialised thematic maps at various scales. As an example of the use of GLIS for agricultural development, a thematic map showing soil suitability for vegetable production was made, which, by area inventory shows that in the County there are 15 197.6 ha of soils suitable for vegetable production, which is only 4.56% of the total area of soil. The second example of the use of GLIS is in physical planning, where the land classification map was made, defining soils of classes 1 through 5, which are protected by the law (N.N. 54/1994) from being used for non-agricultural purposes. Such soils comprise the area of 189 057.0 ha, which is 56.79% of the total area. Thus, these soils must be paid proper attention and protected from uncontrolled and unjustified use for purposes other than agriculture. Other examples of the use of GLIS is in land conservation and development. The specialised map was made showing the requirements for liming, which allows determining the distribution and areas of soils that require this agrotechnical measure.